Cytokine response in cerebrospinal fluid of meningitis patients and outcome associated with pneumococcal serotype - Annelies Müller (Nature Portfolio, 2021)
Abstract Streptococcus pneumoniae causes life-threatening meningitis. Its capsular polysaccharide determines the serotype and influences disease severity but the mechanism is largely unknown. Due to evidence of elevated cytokines levels in the meningeal inflammatory response, we measured 41 cytokines/chemokines and growth factors in cerebrospinal fluid (CSF) samples from 57 South African meningitis patients (collected in the period 2018–2019), with confirmed S. pneumoniae serotypes, using a multiplexed bead-based immunoassay. Based on multivariable Bayesian regression, using serotype 10A as a reference and after adjusting for HIV and age, we found IL-6 concentrations significantly lower in patients infected with serotypes 6D (undetectable) and 23A (1601 pg/ml), IL-8 concentrations significantly higher in those infected with 22A (40,459 pg/ml), 7F (32,400 pg/ml) and 15B/C (6845 pg/ml), and TNFα concentration significantly higher in those infected with serotype 18A (33,097 pg/ml). Although a relatively small number of clinical samples were available for this study and 28% of samples could not be assigned to a definitive serotype, our data suggests 15B/C worthy of monitoring during surveillance as it is associated with in-hospital case fatality and not included in the 13-valent polysaccharide conjugate vaccine, PCV13. Our data provides average CSF concentrations of a range of cytokines and growth factors for 18 different serotypes (14, 19F, 3, 6A, 7F, 19A, 8, 9N, 10A, 12F, 15B/C, 22F, 16F, 23A, 31, 18A, 6D, 22A) to serve as a basis for future studies investigating host–pathogen interaction during pneumococcal meningitis. We note that differences in induction of IL-8 between serotypes may be particularly worthy of future study.